Nordic Walking at Maximal Fat Oxidation Intensity Decreases Circulating Asprosin and Visceral Obesity in Women With Metabolic Disorders - Kantorowicz, Malgorzata; Szymura, Jadwiga; Szygula, Zbigniew; Kusmierczyk, Justyna; Maciejczyk, Marcin; Wiecek, Magdalena (Frontiers in Physiology, 2021)
Objective: Excess visceral adipose tissue is associated with insulin resistance and other metabolic disorders, including deregulation of adipokine secretion, which may be corrected by aerobic exercise training. Asprosin is a novel adipokine responsible for the regulation of appetite and the release of glucose from the liver, and its levels are pathologically elevated in obesity. The aim of the study was to evaluate the effects of 8-week Nordic walking training at maximal fat oxidation intensity (FATmax) on changes in body mass, as well as those in insulin resistance and asprosin levels among young women with visceral obesity and metabolic disorders. Methods: The study was completed by 14 women (30.14±3.63 years) representing low levels of physical activity, visceral obesity (waist circumference 105.50±14.87 cm, BMI 33.85±5.48 kg/m2) and with metabolic disorders, who for 8 weeks (3 times a week, 60 minutes), participated in NW training at the FATmax intensity (61.92±6.71% HRmax, 42.33±8.69% VO2max) controlled on the basis of heart rate (114.21±14.10 bpm). Results: After 4 and 8 weeks of NW training, a significant decrease in the concentration of asprosin, waist and hip circumference, waist-to-height ratio and body adiposity index (p<0.05, large effect size) were found. Conclusion: The 8-week Nordic walking training at an FATmax intensity decreases the concentration of asprosin in the blood as well as visceral obesity in young women with metabolic disorders.